Towards Sustainable Tourism: An In-Depth Study Of Green Entrepreneurship Strategies In Indonesia - Aurilia Triani Aryaningtyas; Yustina Denik Risyanti; Phia Susanti Helyanan (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Sustainable tourism has emerged as a critical global concern in recent years, with increasing attention directed towards the environmental impact of the tourism industry. Indonesia, renowned for its natural beauty and cultural diversity, has witnessed a surge in tourism activities, accompanied by growing environmental challenges. This research paper presents a comprehensive qualitative analysis of green entrepreneurship initiatives within the Indonesian tourism sector. This study utilizes secondary data sources, primarily drawing from previous research journals, to investigate the strategies and practices employed by green entrepreneurs in the Indonesian tourism industry. The research explores the adoption of sustainable and environmentally friendly business models, innovations in eco-friendly technologies, and partnerships for conservation efforts. It also examines the challenges and opportunities faced by green entrepreneurs in their pursuit of sustainability. The findings of this research contribute to our understanding of the role of green entrepreneurship in mitigating the environmental impacts of tourism in Indonesia. By shedding light on successful strategies and identifying areas for improvement, this study aims to guide policymakers, entrepreneurs, and stakeholders toward more sustainable tourism practices. Ultimately, this research seeks to promote the preservation of Indonesia's rich natural and cultural heritage while fostering economic growth through responsible and environmentally conscious entrepreneurship.